PESANTREN MANAGEMENT PROGRAM IN ORDER TO GROWING CHARACTER OF CHILDREN IN CONFLICT WITH THE LAW (ABH) IN LPKA CLASS II BANDUNG - Misra Sumarni (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
AbstractChild protection issues are so real and worrying in society such as the rise of promiscuity, rampant violence, bullying, pornography, stealing, rape, even murder committed by children to friends or family has become a social problem this cannot be solved completely. Children involved in social issues should be given guidance at the Institute for Special Education of Children (LPKA). This study aims to determine the management of pesantren programs to foster the character of manners for Children in Conflict With Law (ABH) from the planning, implementation and evaluation phase. The method used in this study using qualitative methods with descriptive approach case studies. Management of guidance programs conducted by LPKA has been excellent in its implementation but still lacking in its administration. This can be seen from the absence of curriculum, RPP, and even the format of evaluation of this program. Thus the management of this coaching program must be continuously developed.Keywords: Program Management, Character, Children in Conflict With Law